Association Between Inflammatory Biomarkers and Bone Mineral Density in a Community‐Based Cohort of Men and Women12. Issue 8 (August 2014) - Sponholtz, Todd R.; Zhang, Xiaochun; Fontes, Joao D. T.; Meigs, James B.; Cupples, L. Adrienne; Kiel, Douglas P.; Hannan, Marian T.; McLean, Robert R.
<x xml:space="preserve">Abstract</x> Objective Based upon evidence in animal and in vitro studies, we tested the hypothesis that higher serum concentrations of the cytokines interleukin‐6 (IL‐6) and tumor necrosis factor α (TNFα) and the inflammatory marker C‐reactive protein (CRP) would be inversely associated with bone mineral density (BMD) in a community‐based cohort of men and women, with the strongest associations among postmenopausal women not receiving menopause hormonal therapy (MHT). Methods We ascertained fasting serum concentrations of IL‐6, TNFα, and CRP and measured BMD at the femoral neck, trochanter, total femur, and spine (L2–L4) using dual x‐ray absorptiometry in 2, 915 members of the Framingham Offspring Study (1996–2001). We used multivariable linear regression to estimate the difference (β) in BMD at each bone site associated with a 1‐unit increase in log‐transformed serum concentrations of IL‐6, TNFα, and CRP separately for men (n = 1, 293), premenopausal women (n = 231), postmenopausal women receiving MHT (n = 498), and postmenopausal women not receiving MHT (n = 893). Results Inflammatory biomarkers were not associated with BMD in men. Among premenopausal women, there were statistically significant, modest inverse associations between IL‐6 and trochanter BMD (β = −0.030, P < 0.01) and between CRP and femoral neck (β = −0.015, P = 0.05) and trochanter BMD (β = −0.014, P = 0.04). TNFα was positively associated with spine BMD (β = 0.043, P = 0.01). In postmenopausal women receiving MHT, CRP was positively associated with femoral neck BMD (β = 0.011, P = 0.04). There were no associations among postmenopausal women not receiving MHT. Conclusion The lack of consistency in our results suggests that elevated circulating concentrations of inflammatory biomarkers may not be a risk factor for low BMD.